Determination of Educational Technology: Analysis of Online Learning and Learning Styles - Meriyati Meriyati; Anizar Rahayu; Umi Hijriah; Agus Jatmiko (Dinasti International Journal of Education Management And Social Science, 2022)
The Literature Review article Determination of Educational Technology: Analysis of Online Learning and Learning Styles is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Education Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature research are: 1) Educational Technology relates to Online Learning; 2) Educational Technology relates to Learning Styles; and 3) Online Learning relates to Learning Styles. Apart from these exogenous variables that influence the endogenous variables in Educational Technology, there are other factors that influence them, such as: there are many other factors including the Design, Development and Evaluation variables.